The assessment of walking skills: Italian version - Cortese, Maria Daniela; Cernuzio, Gianmarco; Tonin, Paolo; Priftis, Konstantinos; Piccione, Francesco (Frontiers in Neurology, 2025)
Apraxia is a neuropsychological disorder that impairs voluntary, purposeful movements, with “Gait apraxia” specifically affecting walking. Because of the lack of standardized diagnostic tools, in Italian, we translated and adapted the “Assessment of Walking Skills” (AWS) scale, originally developed for identifying gait apraxia in Alzheimer’s patients. The AWS includes 42 items that evaluate trunk and leg movements, useful for comparing the performance between patients and healthy controls. This translation and adaptation represent a critical step toward standardizing the AWS scale for the Italian population.